Tolerance Tourism: A Historical Perspective on Cultural Integration in Glodok Chinatown Jakarta - Insani, Zsarin Astria Puji; Sendra, I Made; Narottama, Nararya (Humaniora: Journal of Indonesia Culture and Society, 2025)
The research examines the multifaceted history of tolerance tourism in Glodok Chinatown, Jakarta, Indonesia, with a focus on the Peranakan Chinese community and its unique cultural heritage. Glodok's development as a tourism destination is examined through the lens of "tolerance tourism", with the region's diverse ethnic and religious groups serving as the primary element in the development of heritage tourism. To understand the impact of events, policies, and social dynamics on tourism growth, the study employs a qualitative thematic approach to analyze historical literature spanning from colonial times to the present. The analysis examines the efforts by government bodies and local stakeholders, including the cultural ambassadors, to promote Glodok Chinatown's cultural heritage while ensuring inclusivity and community empowerment. The research also critically assesses the challenges faced, such as maintaining cultural authenticity amidst commodification and the need for balanced development that empowers local communities alongside economic growth. The research concludes by emphasizing the importance of inclusive tourism policies, effective communication strategies, and sustained stakeholder involvement to achieve truly successful and sustainable tolerance tourism in Glodok Chinatown. By understanding the historical context and the dynamic interactions between various stakeholders in Glodok Chinatown, the study provides valuable insights for the development of culturally sensitive and community-empowering tourism models in similar multicultural settings.